A Review of Pharmacopuncture Treatment for Frozen Shoulder: A Literature Review of Clinical Trials - Seong-Mok Jeong; Sung-Jin Kim; Jin-Young Yoon; Chang Hee Lee; Sung-Eun Shim; Jeong Hyon Kim; Bon Hyuk Goo; Yeon-Cheol Park; Byung-Kwan Seo; Sang-soo Nam; Yong-Hyeon Baek (MEDrang Inc., 2018)
The objective of this study was to review clinical trials of pharmacopuncture treatment for Frozen Shoulder and to evaluate trends in this field. The literature search was performed using PubMed, the Cochrane Library, China National Knowledge Infrastructure, and 5 Korean electronic databases. A combination of "pharmacopuncture," "acupoint injection," "Frozen Shoulder," "adhesive capsulitis," and "periarthritis of shoulder" search terms were used. A total of 9 studies were included in this review. The studies were classified into herbal extract-based (5 types) and animal-based (2 types) pharmacopuncture treatment of Frozen Shoulder. There were 14 different acupoints and Ashi points used in the 9 studies. The total volume of herbal extract-based pharmacopuncture injected was usually between 2 mL and 4 mL, and for animal-based pharmacopuncture it was 1 ml. In most studies of Frozen Shoulder, pain was reduced and function was significantly improved after pharmacopuncture treatment. These results demonstrate that pharmacopuncture alleviates pain and restores function in patients with Frozen Shoulder. Further studies must be conducted on pharmacopuncture for management of Frozen Shoulder.